Security Threats In SDN - Bartlomiej KULIK; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2021)
Software Defined Networking (SDN) means designing network solutions so that they can be controlled and managed dynamically and automatically using appropriate software. SDN architecture solves one of the most serious problems of today's computer networks, which are not very susceptible to changes and reconfiguration so not adapted to the requirements of today's applications that need some network flexibility. Therefore, changing the traditional approach to a more modern, dynamic, ensuring greater flexibility and security is the essence of the work on SDN. In this short article outlines the SDN architecture and types of threats in software defined networks.
Keywords: SDN – Software Defined Networking; SDN security; SDN threats